(untitled) (Research, Society and Development, 2021)
The objective was to evaluate the impact of the implementation of the residency service in oral and maxillofacial surgery and traumatology in a public hospital in Campina Grande – PB, Brazil. 516 medical records were analyzed of patients operated at the Hospital de Emergência e Trauma Dom Luiz Gonzaga Fernandes (HETDLGF), from March 2017 to February 2018 (period without the residency service) and March 2018 to February 2019 (1st year residence service). The results were compiled into a database organized in Microsoft Excel®️ spreadsheets and later analyzed in the SPSS®️ software for Windows 25.0. Among the 516 patients, 236 were operated in the year before residence (mean 19.6 surgeries monthly) and 280 patients were operated in the year of residence (mean 23.3 surgeries per month). It is observed an increase of 44 surgeries, equivalent to more than two months of surgeries compared to the year preceding the implementation of the residency. The average waiting time for the patient for surgery decreased by 2.5 days and the average hospital stay by 2.6 days. The hospital achieved an average savings of R1,102.58 per admission, compared to previous years. Of the total sample, 416 (80.6%) were male and 100 (19.4%) were female. It is concluded that the implementation of a residency service in a public hospital promotes a positive impact, reducing the patient’s waiting time for surgical treatment, the length of hospital stay and, consequently, the financial costs to the hospital.